Hepatic lentiviral gene transfer prevents the long-term onset of hepatic tumours of glycogen storage disease type 1a in mice. (5th January 2015) - Clar, Julie; Mutel, Elodie; Gri, Blandine; Creneguy, Alison; Stefanutti, Anne; Gaillard, Sophie; Ferry, Nicolas; Beuf, Olivier; Mithieux, Gilles; Nguyen, Tuan Huy; Rajas, Fabienne
Abstract: Glycogen storage disease type 1a (GSD1a) is a rare disease due to the deficiency in the glucose-6-phosphatase (G6Pase) catalytic subunit (encoded by G6pc ), which is essential for endogenous glucose production. Despite strict diet control to maintain blood glucose, patients with GSD1a develop hepatomegaly, steatosis and then hepatocellular adenomas (HCA), which can undergo malignant transformation. Recently, gene therapy has attracted attention as a potential treatment for GSD1a. In order to maintain long-term transgene expression, we developed an HIV-based vector, which allowed us to specifically express the human G6PC cDNA in the liver. We analysed the efficiency of this lentiviral vector in the prevention of the development of the hepatic disease in an original GSD1a mouse model, which exhibits G6Pase deficiency exclusively in the liver (L-G6pc −/− mice). Recombinant lentivirus were injected in B6.G6pc ex3lox/ex3lox . SA creERT2/w neonates and G6pc deletion was induced by tamoxifen treatment at weaning. Magnetic resonance imaging was then performed to follow up the development of hepatic tumours. Lentiviral gene therapy restored glucose-6 phosphatase activity sufficient to correct fasting hypoglycaemia during 9 months. Moreover, lentivirus-treated L-G6pc −/− mice presented normal hepatic triglyceride levels, whereas untreated mice developed steatosis. Glycogen stores were also decreased although liver weight remained high. Interestingly, lentivirus-treated L-G6pc −/− mice were protected against the development of hepatic tumours after 9 months of gene therapy while most of untreated L-G6pc −/− mice developed millimetric HCA. Thus the treatment of newborns by recombinant lentivirus appears as an attractive approach to protect the liver from the development of steatosis and hepatic tumours associated to GSD1a pathology.